Xavier Mina an his time - Miranda Rubio, Francisco (Huarte de San Juan. Geografía e Historia, 2018)
The figure of Xavier Mina has always been controversial, exalted by the Mexican nationalism as a national hero and forgotten by his Spanish compatriots. The latest investigations show a liberal man of his time, who fought the absolutism of Ferdinand vii for the free trade against the monopoly of the traders from Cádiz, as well as against the privileges of the clique of the Spanish King. He acquired his liberal ideals in London, where he met Lord Holland and Lord Russell. He attended the Holland House Circle regularly, where he came into contact with the Spanish liberals. He led an expedition to support Morelos and the Mexican Government with the economical help of English and North Americans traders. His arrival into Nueva España coincided with the worst moments of the revolution. The Viceroy Ruiz de Apodaca contributed to the failure of the expeditions, and the supporters of the King finally executed Mina in 1817.